Characterization and optimization of a two-step carbonation process for valorization of recycled cement paste fine powder. (5th April 2021) - Fang, Xiaoliang; Xuan, Dongxing; Zhan, Baojian; Li, Weifeng; Poon, Chi Sun
Abstract: In a previous study, a novel two-step carbonation technique was developed to convert finely crushed hardened cement paste into a calcium-rich and a silica-rich residue. This paper reports a further work on optimizing the two-step carbonation process by studying the influences of a series of experimental variables including particle size, Na2 CO3 concentration, reaction time and temperature, CO2 flow-rate, and CO2 concentration on the carbonation processes. The characteristics of the chemical and physical properties of calcium-rich (mainly calcite) and silica-rich (silica and alumina-silica gel) residues formed were analyzed by using X-ray fluorescence (XRF), powdered X-ray diffraction (XRD), scanning electron microscopy (SEM), and nuclear magnetic resonance (NMR). It was found that the changes in the experimental variables of both Steps 1 and 2 mainly affected the amounts of new products formed, but only slightly changed the chemical structures of the new products. Through a series of comparative tests, the most efficient conditions for the two-step carbonation process was reported. Comparing to the previous exploratory reaction conditions of 24 h stirring and 7 h flow-through carbonation using pure CO2 gas, the optimum conditions would be: i) in Step 1: a 5–10 wt% Na2 CO3 solution, a reaction duration of 5–7 h under ambient temperature, ii) in Step 2: a CO2 gas with a concentration of>50%, and the carbonation ending with a final pH ≤ 9.8 in less than 90 mins. Meanwhile, the estimated CO2 uptake in Step 2 was 0.136 g per gram of RCP. In addition, the supernatant of Step 2 after centrifugation can be recycled and reused as the Na2 CO3 solution in Step 1 for another reaction cycle after pH adjustment by NaOH.